An internal model control design method for failure-tolerant control with multiple objectives. (2nd September 2020) - Mesbah, Ali; Paulson, Joel A.; Braatz, Richard D.
Abstract: The selection of control structure is a critical step in the design of a control system since it can largely affect the achievable control performance. This paper presents a general internal model control (IMC) structure with multiple degrees-of-freedom for the design of control systems with multiple objectives (i.e., reference tracking and load and output disturbance rejection), so that controllers are designed independently of each other. The optimal performance of controllers is shown to remain intact when a controller is taken off-line, for example, due to actuator and/or sensor failures. This feature circumvents the need to redesign the remaining on-line controllers for optimal failure-tolerant control. The proposed control approach is used to derive IMC control structures for multi-loop cascade and coordinated control systems. The performance of the control approach is demonstrated on a simulated thin-film drying process in continuous pharmaceutical manufacturing for several multi-loop control structures and a variety of control-loop component failures.